Implementasi dari Corporate Negligence dan Relevansi Quasi Economic Credentialing dalam Praktik di Rumah Sakit Swasta - Theodorus Hendrik Willem Lumunon; Liju Zet Viany; Butje Tampi; Caecelia J. J. Waha (University of Udayana, 2020)
The prevailing law of the hospital liability for every damage occured by the health professionals in hospital falls into very broad sense and leaving many critical questions about how this definition to be applied. The question addressed whether the hospital may defend it's position by proving that the negligence by the health professionals was caused beyond the hospital guidelines such as the theory of professional liability scheme?. Purpose: to explain the hospital liability based on the corporate negligence theory, and to identify the implementation of economic credential in private hospitals. Method: using the normative juridical method, through legislation approach, concepts and legal comparison and also supported by the data field such focus group discussion. Results: Health professionals can be liabiled if she/he has found deviate by the professional medical standards.The hospital was liabiled for every damage occured by the health professional based on the